Microsurgery training with smartphone - Capkin, Sercan; Cavit, Ali; Kaleli, Tufan (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2018)
Microsurgery is widely used in experimental research models and clinical surgery. However, microsurgical applications require precise technical skills and continuous training. Here, we proposed a low cost, practical microsurgery model, which can be easily applied using smartphones at home or at office. Test platform was created using latex gloves, and a phone holder was then positioned at one side of a table. A smartphone with 10x magnification was secured on the phone holder. Microsurgical device habit, stitching and knotting exercises by making cuts at different angles on the glove model were performed, which was recorded live under the 10x magnification of the phone camera.We believe that the practical microsurgery model presented in this study can form an important part of basic microsurgery education and also act as an alternative training model owing to its ease of application, easy accessibility and low cost.
Keywords: Microsurgery; training model; smartphone